Address to the United Nations Conference on Trade and Development, Geneva, March 25, 1964 - Woods, George D. (World Bank, Washington, DC, 2019)
George D. Woods, the President of the World Bank, remarked that both investment and trade are basic to economic development, which is the essential preoccupation of the Bank. He suggested that, in approaching its agenda, the aim of this Conference must be nothing less than to make a real start in evolving international trade and development policies which are more adequate than those presently prevailing for stimulating economic growth throughout the developing world. One consideration is whether to seek greater price stability through commodity agreements, or to try to mitigate the effects of price fluctuations through some new form of compensatory financing, or to try some new approach altogether. He earnestly urged that governments re-examine the amount of their pledges to IDA in the light of the pressing investment requirements of the developing countries.